2007
DOI: 10.1080/10408440601123446
|View full text |Cite
|
Sign up to set email alerts
|

General Background on the Hypothalamic-Pituitary-Thyroid (HPT) Axis

Abstract: This article reviews the thyroid system, mainly from a mammalian standpoint. However, the thyroid system is highly conserved among vertebrate species, so the general information on thyroid hormone production and feedback through the hypothalamic-pituitary-thyroid (HPT) axis should be considered for all vertebrates, while species-specific differences are highlighted in the individual articles. This background article begins by outlining the HPT axis with its components and functions. For example, it describes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
264
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(279 citation statements)
references
References 409 publications
13
264
0
2
Order By: Relevance
“…Significant transcriptional up-regulation of Pax8 and Nkx2.1a was observed, suggesting that thyroid growth and development were promoted to compensate for the depressed T4 levels. As thyroid transcription factors, Nkx2.1a (TTF1) and Pax8 regulate the expression of NIS and TG in the thyroid system (Kambe et al, 1996;Zoeller et al, 2007), the increased gene transcription of NIS and TG observed in the present study may be controlled by Nkx2.1a and Pax8 to compensate for the reduced T4 levels. A significant up-regulation in transcription of these genes has also been reported in DE-71 exposure to zebrafish larvae concomitant with decreased T4 levels (Yu et al, 2010).…”
Section: Discussionmentioning
confidence: 82%
“…Significant transcriptional up-regulation of Pax8 and Nkx2.1a was observed, suggesting that thyroid growth and development were promoted to compensate for the depressed T4 levels. As thyroid transcription factors, Nkx2.1a (TTF1) and Pax8 regulate the expression of NIS and TG in the thyroid system (Kambe et al, 1996;Zoeller et al, 2007), the increased gene transcription of NIS and TG observed in the present study may be controlled by Nkx2.1a and Pax8 to compensate for the reduced T4 levels. A significant up-regulation in transcription of these genes has also been reported in DE-71 exposure to zebrafish larvae concomitant with decreased T4 levels (Yu et al, 2010).…”
Section: Discussionmentioning
confidence: 82%
“…In the present study, the transcription of slc5a5 and TG genes was significantly upregulated. The transcription of the NIS gene is regulated by thyroid transcription factor (TTF-1, TTF-2) and Pax8, and stimulated by TSH (Zoeller et al, 2007a). Thus, TSH enhances the ability of the thyroid gland to trap iodide.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, exposure to DE-71 significantly upregulated the transcription of CRH and TSH␤ genes. Some reports suggest that THs modulate the expression of TRH and TSH in mammals via a negative feedback mechanism (Elsalini and Rohr, 2003;Zoeller et al, 2007a;Manchado et al, 2008;Chiamolera and Wondisford, 2009). Probably, the modulation of transcription of CRH and TSH genes is influenced by the TH levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormones help regulate metabolic rate by altering expression of membrane ion pumps and can increase glucose oxidation rates in some species (Atkinson et al, 2011). Thyroid hormones can increase the metabolic clearance of cortisol (Thompson, 2007), as well as inducing the release of cortisol at inflammation sites (Zoeller et al, 2007). Under conditions of chronic stress, cortisol promotes the expression of deiodonase enzymes that produce rT3 from T4 (Helmreich and Tylee, 2011).…”
Section: Introductionmentioning
confidence: 99%